Simultaneous detection of major blackleg and soft rot bacterial pathogens in potato by multiplex polymerase chain reaction2. (13th September 2014) - Potrykus, M.; Sledz, W.; Golanowska, M.; Slawiak, M.; Binek, A.; Motyka, A.; Zoledowska, S.; Czajkowski, R.; Lojkowska, E.
Abstract A multiplex polymerase chain reaction (PCR) assay for simultaneous, fast and reliable detection of the main soft rot and blackleg potato pathogens in Europe has been developed. It utilises three pairs of primers and enables detection of three groups of pectinolytic bacteria frequently found in potato, namely: Pectobacterium atrosepticum, Pectobacterium carotovorum subsp. carotovorum together with Pectobacterium wasabiae and Dickeya spp. in a multiplex PCR assay. In studies with axenic cultures of bacteria, the multiplex assay was specific as it gave positive results only with strains of the target species and negative results with 18 non‐target species of bacteria that can possibly coexist with pectinolytic bacteria in a potato ecosystem. The developed assay could detect as little as 0.01 ng µL–1 of Dickeya sp. genomic DNA, and down to 0.1 ng µL–1 of P. atrosepticum and P. carotovorum subsp. carotovorum genomic DNA in vitro. In the presence of competitor genomic DNA, isolated from Pseudomonas fluorescens cells, the sensitivity of the multiplex PCR decreased tenfold for P. atrosepticum and Dickeya sp., while no change was observed for P. carotovorum subsp. carotovorum and P. wasabiae. In spiked potato haulm and tuber samples, the threshold level for target bacteria was 101 cfu mL–1 plant extract (102 cfu g–1 plant tissue), 102 cfu mL–1 plant extract (103 cfu g–1 plant tissue), 103 cfu mL–1 plant extract (104 cfu g–1 plant tissue), for Dickeya spp., P. atrosepticum and P. carotovorum subsp. carotovorum/P. wasabiae, respectively. Most of all, this assay allowed reliable detection and identification of soft rot and blackleg pathogens in naturally infected symptomatic and asymptomatic potato stem and progeny tuber samples collected from potato fields all over Poland.